Reservations to human rights treaties - McCall-Smith, Kasey Lowe (The University of Edinburgh, 2012)
This thesis examines the default application of the 1969 Vienna Convention on the Law of Treaties reservation rules to reservations to human rights treaties. The contemporary practice of formulating reservations allows states to unilaterally modify their treaty obligations following the conclusion of negotiations. Though multilateral treaties address a broad spectrum of subjects and are negotiated using a variety of methods, all treaties are governed by the same residual reservation rules of the Vienna Convention when there is not a treaty-specific reservation regime in place. The Vienna Convention system is only engaged if a state seizes the opportunity to determine whether a reservation is valid pursuant to default rules or if a challenge regarding the validity of a reservation is brought before another competent mechanism of review, such as a dispute resolution mechanism. Even when applied, the Vienna Convention rules are ambiguous at best and have been criticised since their inception due to the high degree of flexibility in their application, especially in relation to human rights treaties. In light of the inherent flaws of the Vienna Convention reservation regime and the structural characteristics of human rights treaties, rarely will a reserving state be deprived of the benefit of the reservation even if it is determined to be invalid by another State Party. Though the consequences of an invalidity determination are more concrete when the decision is taken by a dispute resolution mechanism, such as a court, seldom are disputes over the validity of a reservation to a human rights treaty submitted to a competent mechanism. Using the core UN human rights treaties as a case study this research highlights that the past thirty years have revealed a practical impasse in treaty law when the default reservation rules are relied upon to regulate reservations to human rights treaties. Reservations of questionable validity gain the same status as valid reservations because the Vienna Convention rules do not address the consequence for a reservation determined to be invalid outwith the traditional inter se application of the reservation between the reserving and objecting states, which is not logical in the context of a human rights treaty. Against this background, this thesis examines whether the default reservation rules adequately govern reservations to human rights treaties. The conclusion affirms that the Vienna Convention reservation regime can regulate reservations to human rights treaties but only if there is a clearly defined final view on the validity of a reservation taken by an organ other than the state. Therefore, it is argued that treaty-specific supervisory mechanisms attached to each of the core UN human rights treaties should be invested with the competency to serve a determinative function with respect to evaluating reservations to human rights treaties in order to facilitate a stronger basis for the international human rights system.
Keywords: treaties; human rights; reservations; international law; treaty bodies; Vienna Convention on the law of Treaties